The effect of financial performance, company size, and gross domestic product on abnormal returns - Ahmad Abros Mustofa; Yulis Maulida Berniz; Adi Susanto (Jurnal Penelitian, 2022)
This study focuses on the effect of financial performance, firm size, and gross domestic product on abnormal returns. Financial performance is measured by proxies for liquidity, profitability, earnings per share, leverage, and market value. The object of this study was manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020 and samples were taken using a purposive sampling technique so that a sample of 114 manufacturing companies was obtained. The analysis technique in this study uses multiple linear regression analysis. The results showed that liquidity (CR), earnings per share, leverage (DER), market book value (MBR), and firm size had no effect on abnormal returns. Profitability (ROE) has a positive effect on abnormal returns, and the gross domestic product has a negative effect on abnormal returns.